Dr. William L. Venning, Jr. - L. Davis Phillips (Coy C. Carpenter Library, 1944)
Info from: BGSM Bulletin. 1943-45. The Gray and White Matter. 1944-46.
Dr. William L. Venning came to Bowman Gray School of Medicine in 1943 as an Assistant in Pediatrics and was named Instructor of Pediatrics from 1944-1946.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth